DETERMINATION OF CRITICAL VALUE OF pH OF GEL FORMATION IN SILICATE-ALKALI MIXTURES OF VARIOUS COMPOSITION - Titova, Оlga; Stoliarova, Natalia; Hrushak, Zoia; Kravchuk, Tetiana (Proceedings of National Aviation University (archive), 2017)
Purpose: The aim of this study is the research of a possibility of a direct and reverse titration usage for the critical pH determination. pH value change of the silicate-alkali mixture was analyzed while addition of alkalis, salt water and sodium hydrogen carbonate solutions. Methods: Methods of direct and reverse titration were used for the determination of various additives influence on results of pH measuring of sodium silicate mixtures. Results: Additives method or reverse titration of the alkali solution are the most appropriate methods for the determination of free alkali content in silicate solutions. Dilution of silicate-alkali solutions by salt water or its model leads to the faster decrease of pH value, than in case of water without any salts of hardness. Hydrogen carbonates influence should be accounted when execution of accurate calculations used in the development of silicate-alkali mixtures usage technology. Discussion: Alkali-silicate mixtures would be solutions for a long time when filtration proceeds in the porous medium at рН > рНcrit. The time of such solutions existence must be characterized by a before inductive period. When reaching the critical pH value, a gel is formed during an inductive period or the time of gel formation. As a rule, the before inductive period is in ten times or even more greater than the time of gel formation.